2020
DOI: 10.1590/0103-8478cr20190452
|View full text |Cite
|
Sign up to set email alerts
|

Potential of parents and hybrids experimental of the yellow melon

Abstract: Melon or muskmelon (Cucumis melo L.) is of considerable economic importance in Brazil. Nearly all the cultivars currently grown are hybrids. Heterosis has been used to advantage in the melon plant, and the use of uniform hybrids is one of the reasons for successful cultivation. The aim of the present study was to evaluate the agronomic potential of yellow melon lines and hybrids. An experiment was conducted in randomized blocks with three replications to evaluate 24 hybrids generated by crosses among three eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(18 reference statements)
2
1
0
1
Order By: Relevance
“…Therefore, for these traits, the contribution of dominance variance was higher than the additive genetic variance (Table 2). These findings were consistent with other studies [46][47][48][49]. However, additive gene and both additive and dominant gene actions have also been reported to be predominant in the genetic control of these traits [15,50,51,57].…”
Section: Biochemical Fruit Quality Traitssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, for these traits, the contribution of dominance variance was higher than the additive genetic variance (Table 2). These findings were consistent with other studies [46][47][48][49]. However, additive gene and both additive and dominant gene actions have also been reported to be predominant in the genetic control of these traits [15,50,51,57].…”
Section: Biochemical Fruit Quality Traitssupporting
confidence: 93%
“…The significance of both GCA and SCA variances indicated the role of both additive and nonadditive gene effects in governing these traits. Similar gene actions in controlling the fruit yield, number of fruits per vine and average fruit weight have been reported in previous studies in muskmelon [43][44][45][46]. However, Saha et al [47] and Badami et al [48] reported the dominant gene action to be responsible for controlling the yield-related traits, such as the fruit weight.…”
Section: Genetic Diversity Among Ten Parental Lines and Hybrid Perfor...supporting
confidence: 73%
“…Differences of genotypes are associated with variability that exists between materials [11]. Response of additive effects (GCA) and non-additive effects (SCA) is involved in genetic control of trait [12]. Results of general and specific combining ability provide relevant information on parents and progeny to continue advancing in breeding program.…”
Section: Resultsmentioning
confidence: 99%
“…As cultivares de melão de maior expressão nacional são do tipo Pele de Sapo, Amarelo, Cantaloupe e Gália, com tendência crescente a exploração de híbridos pelo seu potencial produtivo, especialmente quando irrigado (Lima, 2015;Cavalcante Neto et al, 2020). Irrigação esta que é promovida predominantemente pelo sistema de gotejamento, por evitar molhar a parte aérea da planta, permitir maior controle na quimigação e maior eficiência de uso da água.…”
unclassified